Potentials and Pitfalls of Cross-Translational Models of Cognitive Impairment - Al Dahhan, Noor Z.; De Felice, Fernanda G.; Munoz, Douglas P. (Frontiers in Behavioral Neuroscience, 2019)
A number of clinical disorders that are either neurodevelopmental or neurodegenerative exhibit significant cognitive impairments that require some form of intervention. However, the current paucity of pro-cognitive treatments that are available, due to the lack of knowledge of biological targets and symptomologies, impedes the treatment of individuals with cognitive impairments. In this review, we explore three critical steps that need to be established in order to lead to the development of effective and appropriate treatments for cognitive impairments. The first step specifically involves the ability to efficiently reproduce and standardize current animal models of disease. The second step involves establishing well-controlled and standardized animal models across different species, such as rodents and monkeys, that link to human disease conditions. The third step involves building these animal models from both a translational and a reverse translational perspective in order to gain critical insight into the aetiologies of specific cognitive impairments and the development of their early physiological and behavioral biomarkers. This bidirectional translational approach is important to improve the investigation of disease biomarkers, the underlying mechanisms of novel therapeutics on cognition, and to validate preclinical findings of drug discovery. Overall, even though animal models play an important role in investigating the pathophysiological processes and mechanisms associated with typical and atypical behavior, we discuss the ongoing challenges associated with these three critical steps of cross-translational research that has led to the current lack of success of developing effective new compounds for potential treatments and suggest approaches to stimulate advances in the field.